Saikosaponin D Ameliorates Mechanical Hypersensitivity in Animal Models of Neuropathic Pain - Lee, Gyeongbeen; Nam, Yeon-Ju; Kim, Woo Jung; Shin, Bo Hye; Lee, Jong Suk; Park, Hwan Tae; Kim, Pansoo; Lee, Ji Hyun; Choi, Yongmun (Planta Medica International Open, 2020)
We have previously identified saikosaponins as transient receptor potential ankyrin 1 antagonists and showed that saikosaponin D improves neuropathic pain induced by the anticancer drug vincristine in mice. In order to gain more insight into the therapeutic effects of saikosaponin D, we tested saikosaponin D in animal models of neuropathic pain induced by either streptozotocin, which mimics diabetes, or paclitaxel, a commonly used chemotherapy treatment. Our findings indicate that although saikosaponin D improved pain outcomes in neuropathic pain models, the mechanisms underlying the therapeutic effects of saikosaponin D appear to differ between streptozotocin- and paclitaxel-induced pain. Streptozotocin-induced neuropathic pain was significantly alleviated 30 minutes after oral administration of saikosaponin D, while 1-day oral administration of saikosaponin D had little effect on paclitaxel-induced mechanical hypersensitivity. Attenuation of paclitaxel-induced mechanical hypersensitivity was evident only after repeated administration of saikosaponin D. Although the mechanisms underlying the therapeutic effects of saikosaponin D remain to be elucidated, our results shed new light on the therapeutic potential of saikosaponin D in the management of neuropathic pain caused by diabetes or chemotherapy.
Keywords: Saikosaponin D neuropathic pain diabetes chemotherapy